(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This study examines approaches to improving the organizational and economic mechanisms of creative industries with a specific focus on museum management in Uzbekistan. As cultural institutions increasingly contribute to economic development and social cohesion, their governance and financing systems require modernization aligned with global creative economy trends. The research employs a comparative and institutional methodology, integrating theoretical frameworks of the creative economy, cultural management, and public–private partnership models. Empirical insights are drawn from the experiences of the United Kingdom, South Korea, the United States, France, and Uzbekistan. The findings reveal that sustainable museum development depends on diversified funding, digital transformation, human capital development, and integration with the broader creative ecosystem. The study proposes strategic recommendations for Uzbekistan to strengthen institutional frameworks, enhance managerial autonomy, and attract private investment while safeguarding cultural identity. The results contribute to a deeper understanding of how creative industry mechanisms can serve as engines of innovation, employment, and cultural diplomacy in emerging economies.